Intersectional factors in youth transition: Stories of vocational high schools’ graduates in Indonesia - Ramadhani, Indah Sri; Isbah, M Falikul; Azca, Muhammad Najib (Center for Sociological Studies and Community Developmen, 2025)
This study examines the challenges faced by vocational high school graduates in their transition to employment and their strategies for overcoming these challenges. Vocational high school is advocated as a provider of skilled and job-ready graduates to solve unemployment problems. However, employment statistics show that vocational high school graduates account for the largest share of unemployment in Indonesia. This study aims to improve our understanding of this anomaly. The data in this paper were collected through in-depth interviews with vocational high school graduates in Yogyakarta, with a balanced representation of gender, geographic location, and specialization. We found that most graduates successfully obtained employment immediately after graduation. However, most of the employment is of low quality, indicating vulnerability in the transition. Their challenges emerge at different stages: before, during and after their schooling. This study also highlights the institutional role of vocational high schools in facilitating the school-to-work transition. Thus, this study contributes to the current discourse on youth transition by highlighting the intersectionality of factors influencing the transition of vocational high school graduates to the labor market and by pointing to the central role of the school in supporting their transition process.